2016
DOI: 10.1002/mawe.201600608
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of through‐hardening of SAE 52100 steel bearings – Part II: Validation at industrial scale

Abstract: In this study, the material dataset presented in part I of this article is validated at industrial scale in batch through-hardening of bearing races. The material dataset acquired is implemented in a commercial heat treatment simulation software. Heat transfer coefficients for the oil and salt bath are determined by using a commercial standard quench probe. Zone temperatures and transfer times of the roller-belt furnace are measured directly from the system.Through-hardening of inner ring (IR) of 6813 bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…5 h, followed by air cooling (20 °C) for 1.5 h. The quenched block was then tempered at 565 °C for about 48 hours to reduce the level of the residual stresses produced during quenching. While the tempering could very slightly affect the quenchinduced distortions, the dimensional changes are, however, considered relatively negligible in this case, considering the large size of the block[21].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…5 h, followed by air cooling (20 °C) for 1.5 h. The quenched block was then tempered at 565 °C for about 48 hours to reduce the level of the residual stresses produced during quenching. While the tempering could very slightly affect the quenchinduced distortions, the dimensional changes are, however, considered relatively negligible in this case, considering the large size of the block[21].…”
mentioning
confidence: 92%
“…For example, the size and the shape of the part asymmetrically affect the heat transfer within the part, the phase transformation at different locations, and hence, the distribution of the residual stresses and properties. This can only be circumvented if a 3D modeling approach is used [4,13] and accurate material data (e.g., properties of each phase) are employed [21].…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] However, there may still be deviations in the prediction of the internal temperature of large‐sized parts during quenching. [ 11 ] The accumulation of temperature data has been limited, and most of the results are predictions without experimental verification. The effect of temperature change at different positions on the microstructure and cooling characteristics of steel during quenching has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been found that the use of static values of HTC in FEM models yields results substantially different compared to models employing temperature-dependent HTC for the purpose of simulating cooling curves and stress profiles both in gas [9,10] and liquid quenching [7]. Therefore, the use of a temperature-independent HTC should be avoided in oil and water quenching baths, although it may be useful in salt baths [11]. There has been a considerable number of papers where the characteristic time-and temperature-dependent HTC curves for a Jominy end quench test [12][13][14][15] have been studied and validated [16,17].…”
Section: Introductionmentioning
confidence: 99%